Lightning effects on distribution transformers and reliability of power distribution systems in Colombia (2015)
Failure rates of rural power systems are statistically studied based on lightning parameters and a two-state weather model (normal and adverse). Lightning information is matched with geographical coordinates of 251,024 power transformers in a vast area in central Colombia. An important portion of transformers present failure rates 45 times higher than normal, and very large overhead lines, representing a high portion of the total system, present very high failure rates over 75 times higher than in normal weather conditions.